Antinociceptive and anti-inflammatory potential of Rhododendron arboreum bark. (July 2016) - Nisar, Muhammad; Ali, Sajid; Muhammad, Naveed; Gillani, Syed N; Shah, Muhmmad R; Khan, Haroon; Maione, Francesco
Rhododendron arboreum Smith. (Ericaceae), an evergreen small tree, is one of the 1000 species that belongs to genus Rhododendron distributed worldwide. In folk medicine, as various parts of this plant exhibit medicinal properties, it is used in the treatment of different ailments. The present study was designed to evaluate the potential anti-inflammatory and antinociceptive effects of methanolic extract of R. arboreum bark, followed by activity-guided fractionation of n-hexane, n-butanol, chloroform, ethyl acetate and aqueous fractions. The ethyl acetate fraction (200 mg/kg i.p.) showed the maximum analgesic effect (82%) in acetic acid-induced writhing, followed, to a less extent, by crude extract and chloroform fraction both at a dose of 200 mg/kg i.p. (65.09% and 67.89%, respectively). In carrageenan-induced mouse paw oedema, the crude extract and its related fractions displayed in a dose-dependent manner (50–200 mg/kg i.p.) an anti-inflammatory activity for all time-courses (1–5 hrs). For the active extract/fractions (200 mg/kg i.p.), the maximum effect was observed 5 h after carrageenan injection. These evidences were also supported by in vitro lipoxygenase inhibitory properties. In conclusion, R. arboreum crude methanolic extract and its fractions exhibited anti-inflammatory and antinociceptive effects. For these reasons, this plant could be a promising source of new compounds for the management of pain and inflammatory diseases.